(untitled) (Iranian Journal of Kidney Diseases, 2017)
Presentation of rheumatoid arthritis (RA) with renal complications is very rare without articular symptoms. We here report a case of a 23-year-old woman, presenting with the edema of the extremities, no relevant previous medical history, and the features of acute tubular injury in her percutaneous kidney biopsy. Following the incidental notification of a positive rheumatoid factor test, other immunologic tests including anticyclic citrullinated peptide and antimutated citrullinated vimentin were performed, the positive results of which favored the diagnosis of RA. Administration of rituximab led to the complete remission of the disease. Six weeks later, along with steroid dose reduction, the symptoms of arthralgia was observed, which was managed with methotrexate. Nephrotic syndrome could be rarely the first manifestation of RA, and screening of specific RA autoantibodies might be considered as part of diagnostic evaluations in nephrotic syndrome workup.